Assessment of water accessibility and quantity in Ilorin south local government area - Ifabiyi, I.P.; Geoffrey, E.O.; Salami, A.A. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Insufficient supply of treated pipe borne water results in the population seeking alternative sources in order to offset the huge short fall in water supply. This study aimed at assessing water accessibility and quantity supply in Ilorin South Local Government Area of Kwara State, Nigeria. Data used in this study were mainly primary which were obtained from field survey through questionnaire administration and personal field observations. A total of 400 questionnaires were administered to respondents in 40 households using systematic random sampling technique. The minimum Basic Water Requirement (BWR) per person per day, and Water Accessibility Indicator (WAI) were adopted. Descriptive statistical techniques were used for the analyses. The findings from the study revealed that the minimum Basic Water Requirement for the study area is 51.5 liters respectively, while Water Accessibility Indicator revealed that respondents do not have access to water in terms of distance and time. The results obtained indicate that residents suffer from some degree of water scarcity and stress and if there is no prompt intervention from government and well-meaning Nigerians, water crisis would shoot up astronomically in the study area. There is need to improve water supply to residents, especially for those in Akanbi ward V, and water collection points should be located proximate to residents’ houses in this study area.